A Trojan Horse in the Citadel of Stories? - Hartley John (Cultural Science)
Digital storytelling is an international movement for self-representation and advocacy, especially in educational, arts, and therapeutic communities. It has begun to attract a significant body of scholarship including publications and conferences. Australia has been an important player in all of these developments. In this presentation I explore some of the issues that have emerged for activists and scholars, including the problem of how to ‘scale up’ from self-expression to communication (i.e. self-marketing), and the question of the role that stories play in constituting ‘we’-communities (or ‘demes’).